FORMULASI SEDIAAN MOUTHWASH EKSTRAK ETANOL BUNGAMAWAR MERAH (Rosa damascena Mill) SEBAGAI ANTIBAKTERI TERHADAP Streptococcus mutans - Nurfitria Junita; Nielma Auliah; Wantry Diasny (BORNEO JOURNAL OF PHARMASCIENTECH, 2020)
It has been conducted a research about Formulation of Red Rose Ethanol Extract ofMouthwash (Rosa damascena Mill) as Antibacterial toward Streptococcus mutans. Thisresearch aim at knowing the activity of Red Rose Ethanol Extract of Mouthwash (Rosadamascena Mill) as Antibacterial toward Streptococcus mutans. In this study, usingexperimental research by formulating the ethanol extract of red rose (Rosa damascena Mill)mouthwash, then tested against Streptococcus mutans bacteria using the agar diffusionmethod. The ethanol extract of red rose (Rosa damascena Mill) mouthwash was prepared inthree concentrations, namely 1%, 3%, 5%, and control solution. The various concentrationswere tested for their antibacterial activity and an evaluation of the Mouthwash byorganoleptic observation, pH and cycling test. Meanwhile, the antibacterial activity test usedagar diffusion method using agar well diffusion. Results of the measurement of the largestaverage inhibition zone at a concentration of 5% of 21.4 mm. Result showed that physicalstability of mouthwash tended to stable on the low temperature storage (4°C) and had aninhibitory level in strong category in obstructing the growth of Streptococcusmutans